The Role of Legal Education in Raising Public Awareness for Corruption Prevention in Indonesia - Yunita Intan Nur Aini; Friska Ayu Purnama (Konsultan Jurnal Ilmiah Indonesia, 2026)
Corruption remains a major problem that hinders law enforcement and development in Indonesia. Meanwhile, public legal awareness as a means of corruption prevention has not received adequate attention. This research aims to analyze the relationship between public legal awareness and the effectiveness of corruption prevention based on a literature review of various relevant journals. The study employs a qualitative approach and selects 12 articles from a total of 20 journals, followed by data extraction regarding the variables of legal awareness and corruption prevention, and a thematic analysis of the research findings. The results of this study indicate that the low legal awareness observed is caused by weak public interaction with law enforcement. This is compounded by uncertainty in law enforcement, a culture that is permissive of violations, and a lack of legal education. Meanwhile, efforts to prevent corruption are still severely lacking due to gaps in the digital monitoring system, weak public oversight, and very minimal community participation. In conclusion, corruption prevention efforts are highly determined by the level of public legal awareness. Therefore, it is very important to be more systematic in providing community-oriented legal education.